A Review Coastal Waters in Lombok Island: An Aproach for Sustainable Development - Dermawan, Awan; Mujib, Abd Saddam (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Coastal waters play a vital role in supporting ecological balance and socio-economic activities in island regions such as Lombok, Indonesia. Rapid tourism growth, coastal settlements, and marine transportation have increased environmental pressures on these ecosystems. This study aims to provide a comprehensive overview of the ecological condition of Lombok’s coastal waters through a Systematic Literature Review (SLR) of ten scientific articles published between 2014 and 2025. The review follows the PRISMA protocol, focusing on themes of water quality, mangrove and coral reef ecosystems, pollution, and coastal management. The analysis reveals that most coastal areas in Lombok still meet the national seawater quality standards (PP No. 22/2021), with parameters such as temperature, salinity, and dissolved oxygen remaining within optimal ranges. However, nutrient enrichment and trace metal accumulation have been detected in high-activity zones like Mandalika and Teluk Kodek. Mangrove and coral ecosystems in Gili Petagan and Gili Matra remain relatively healthy, supporting conservation and eco-tourism potential. The findings emphasize the need for integrated, science-based management involving community participation to maintain ecological stability while promoting sustainable blue economy development toward Indonesia’s 2045 Vision.